Multi‐faceted nature of managing disasters - Kulatunga, Udayangani (International Journal of Strategic Property Management, 2010)
„Multi‐faceted nature of managing disasters” International Journal of Strategic Property Management, 14(4), p. 283-286. First Published Online: 10 Feb 2011